How does the government reduce unemployment? Legal Policy Analysis of the Government's Role in Strengthening SMEs in Indonesia - Auliya Rochman (Universitas Negeri Semarang, 2021)
Micro, Small and Medium Enterprises (MSMEs) are proven to be the main movers in the real sector that have a direct effect on national economic growth, especially to reduce unemployment. This research is a normative research with a legal approach, historical approach, comparative and conceptual approach. There is a problem regarding the role of the government regarding MSMEs in reducing unemployment and increasing economic growth considering that the Indonesian State is currently only actively promoting the economic development sector. In Indonesia, a developing country that needs a lot of improvement in the economic sector, especially small and medium businesses. Through Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises (MSMEs), the government hopes that through the role of MSMEs, the Indonesian economy will run well to increase job vacancies and reduce unemployment.